A high-flux aromatic polyamide reverse osmosis membrane and preparation method thereof

By introducing indole carboxylic acid compounds and organotin additives into the reverse osmosis membrane, and forming a polyamide desalination layer through interfacial polycondensation reaction, the existing reverse osmosis membrane has been solved by insufficient flux increase, low desalination rate and long-term operation. The serious problem of flux attenuation achieves the balance of high throughput and high desalination rate.

CN115920673BActive Publication Date: 2025-02-18WANHUA CHEM GRP CO LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202211596952.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-12
Publication Date
2025-02-18
Estimated Expiration
2042-12-12

AI Technical Summary

Technical Problem

The existing reverse osmosis membrane has insufficient flux increase at low pressure, low desalination rate, and severe long-term operation flux attenuation, which cannot meet the needs of household water purifiers.

Method used

A high-throughput aramid reverse osmosis membrane is adopted, which is composed of a non-woven fabric, a porous polysulfone support layer and a polyamide formed by an interfacial polycondensation reaction between a m-phenylenediamine aqueous solution and a phenylenediamine tricarboxylic acid chloride solution. The desalted layer consists of a carboxylic acid compound of indole and an organic tin additive in the oily solution.

Benefits of technology

It achieves high throughput and high desalination rate at lower pressures while reducing long-term running flux attenuation, meeting the needs of household water purifiers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003993444110000091
    Figure BDA0003993444110000091
  • Figure BDA0003993444110000101
    Figure BDA0003993444110000101
  • Figure BDA0003993444110000111
    Figure BDA0003993444110000111
Patent Text Reader

Abstract

The present invention provides a high-flux aromatic polyamide reverse osmosis membrane and a preparation method thereof. The reverse osmosis membrane comprises a non-woven fabric, a polysulfone porous support layer and a polyamide desalination layer, wherein the polyamide desalination layer is formed by an interfacial polycondensation reaction of an aqueous solution of metaphenylenediamine and an oily solution of trimesoyl chloride. The reverse osmosis membrane provided by the present invention has the characteristics of high flux, high desalination rate and low flux attenuation during long-term operation. When the raw water is 25°C and the concentration of sodium chloride is 250 mg / L, and the operating pressure is 0.41 MPaG, the desalination rate of the reverse osmosis membrane is above 98.0%, and the permeate flux is 60.0 L / (m 2 h) or more, and after continuous operation for 90 hours, the permeate flux attenuation is less than 15%. The membrane provided by the present invention can be used in the fields of household water purifiers, pure water manufacturing and industrial wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of reverse osmosis membranes, and in particular relates to a high-flux aromatic polyamide reverse osmosis membrane and a preparation method thereof. Background Art

[0002] In recent years, with the improvement of people's living standards and the frequent occurrence of water pollution incidents, people are paying more and more attention to the safety of drinking water quality. As one of the most effective desalination methods, reverse osmosis membrane technology is not only widely used in seawater desalination, ultrapure water production and industrial wastewater treatment and reuse, but can also be used in household and commercial water purifiers to reduce the content of calcium, magnesium and other ions in tap water, remove harmful heavy metals and organic matter, and ensure the health of people's drinking water. In order to reduce the waiting time for water purifiers to make water and reduce the ratio of wastewater to pure water, it is necessary to provide a reverse osmosis membrane with high flux and high desalination rate at lower pressure.

[0003] As a commercial aromatic polyamide reverse osmosis membrane obtained by interfacial polymerization of m-phenylenediamine and trimesoyl chloride on the surface of a polysulfone-based membrane, in addition to optimizing the ratio of m-phenylenediamine and trimesoyl chloride monomers, the means of improving membrane flux include: adding isopropanol and other alcohol solvents (CN1104939C, CN1170627A), phosphate ester complexing agents (CN1210093C, CN1441693, CN210093C, CN104470627A), carboxylic acids or carboxylic acid esters (CN1328483A) and other additives to the aqueous phase or oil phase to regulate the interfacial polycondensation process and optimize the polyamide layer structure; using isopropanol, ethanol, benzyl alcohol, etc. Polar pure solvents dissolve the oligomers in the polyamide layer and the polyamide segments are re-stacked and entangled (CN111545065A); chemical reagents such as sodium hypochlorite (US5876602, CN1103625C) or nitrous acid (CN105377406A, CN105848765B, CN105873666A, CN106170333B, CN106257977B, CN108348869A, CN102665881A, CN103025412A, CN105026022A) are used to change the types and proportions of groups inside the polyamide layer. On the one hand, these methods have limited improvement in the flux of the reverse osmosis membrane, and on the other hand, most of them are even achieved by reducing the cross-linking degree of the polyamide and sacrificing the membrane desalination rate. This loose desalination layer is extremely unstable. Although the initial flux is high, the flux decays severely during use and cannot meet the needs of household water purifiers.

[0004] As mentioned above, although various means have been disclosed to increase the flux of reverse osmosis membranes, there are still problems such as insufficient flux increase, low desalination rate and serious flux attenuation in long-term operation. Summary of the invention

[0005] The purpose of the present invention is to provide an aromatic polyamide reverse osmosis membrane with high flux, high desalination rate and low flux attenuation during long-term operation, which can overcome the problems of insufficient flux improvement, low desalination rate and serious flux attenuation during long-term operation.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:

[0007] A high-flux aromatic polyamide reverse osmosis membrane comprises a non-woven fabric, a polysulfone porous support layer and a polyamide desalination layer, wherein the polyamide desalination layer is formed by an interfacial polycondensation reaction of an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride; wherein the oily solution contains an indole carboxylic acid compound and an organic tin additive.

[0008] The indole carboxylic acid compound is a class of compounds containing both an indole structure and a carboxylic acid group in the molecule, and its representative compound indoleacetic acid is an important plant growth hormone. The inventor unexpectedly found through research that the indole carboxylic acid compound is introduced into the polyamide desalination layer, and combined with the phosphate in the water phase and the methylbenzene and organic tin additives in the oil phase, the permeation flux of the reverse osmosis membrane can be greatly improved while maintaining a high desalination rate. The possible principle of the synergistic effect of the organic tin additive and the indole derivative is: (1) the organic tin compound is a metal organic compound in which tin and carbon atoms are directly connected, and is mainly used as a catalyst auxiliary and stabilizer, which slows down the polycondensation reaction, makes the molecular weight distribution of the formed polyamide more uniform, and increases the permeable channels; (2) the indole structure contains a secondary amine group, which can react with the acyl chloride group in the oil phase, and then participate in the process of interfacial polymerization to form the polyamide desalination layer, and the carboxylic acid group in the molecule can adjust the content of the carboxylic acid group inside the polyamide desalination layer, provide more hydrophilic permeation channels, and then improve the permeation flux of the reverse osmosis membrane.

[0009] In the present invention, in the molecular structure of the indole carboxylic acid compound, the hydrogen on the nitrogen atom of the indole ring is not substituted, the indole ring has only one substituent, and the substituent is an alkyl acid substituent containing 1 to 5 carbon atoms; preferably, the indole carboxylic acid compound is selected from one or more of indole-2-carboxylic acid, indole-3-carboxylic acid, indole-4-carboxylic acid, indole-5-carboxylic acid, indole-6-carboxylic acid, indole-7-carboxylic acid, and 3-indolebutyric acid.

[0010] In the present invention, at least two alkyl groups or phenyl groups in the molecular structure of the organotin auxiliary are directly connected to the tin atom; preferably, the organotin auxiliary is selected from one or more of dimethyltin dichloride, hexa-n-butyltin, and tetraphenyltin.

[0011] In the present invention, the aqueous phase solution contains phosphate ester, preferably triethyl phosphate.

[0012] In the present invention, the oil phase solution contains methylbenzene, preferably 1,3,5-trimethylbenzene.

[0013] The base membrane of the polyamide reverse osmosis membrane is generally used as a physical support layer for the thinner polyamide desalination layer, which gives the entire reverse osmosis membrane mechanical strength, but it does not have the interception performance of small molecular organic matter and salt ions. The base membrane consists of a non-woven fabric substrate and a porous support layer. The following parameters related to the base membrane having a non-woven fabric substrate and a porous support layer are selected as the parameters commonly used in the art.

[0014] In one embodiment, the nonwoven fabric substrate is used as the physical support material of the porous support layer to provide mechanical strength and to form a porous support layer with uniform thickness and surface pore size.

[0015] In one embodiment, the material of the non-woven fabric substrate may preferably be polyethylene, polypropylene, or polyethylene terephthalate (PET for short). In terms of hydrophilicity, mechanical stability, and thermal stability, polyethylene terephthalate is more preferred.

[0016] In one embodiment, the thickness range of the nonwoven fabric substrate is preferably in the range of 20 to 100 μm, and more preferably in the range of 80 to 90 μm. When the thickness of the nonwoven fabric is below 60 μm, the strength of the nonwoven fabric itself is not enough to serve as a physical support for the porous support layer, and the base membrane or reverse osmosis membrane formed therefrom has the risk of rupture in the transverse or longitudinal direction, and cannot meet the requirements. When the thickness of the nonwoven fabric is above 100 μm, although its strength as a physical support is sufficient, the thickness of the reverse osmosis membrane obtained in the end is too thick. On the one hand, the filling membrane area of ​​the membrane element or assembly made therefrom is too low, affecting the water production of a single membrane element or assembly. On the other hand, the amount of unreacted substances (mainly aromatic polyamines) remaining in the nonwoven fabric substrate during the membrane preparation process increases, making it difficult to clean, and finally causing the membrane permeation flux to decrease, and the acid and alkali cleaning resistance will also decrease. From the perspective of physical support strength, the filling membrane area of ​​the membrane element or assembly, and membrane performance, it is more preferred that the thickness range of the nonwoven fabric substrate is in the range of 80 to 90 μm. The thickness deviation range of the nonwoven fabric substrate is preferably less than ±5 μm, and more preferably less than ±3 μm. If the thickness deviation of the nonwoven fabric substrate is too large, it is difficult to apply the casting solution for the porous support layer on the surface of the nonwoven fabric substrate using a scraper or a slot die, and the thickness of the polysulfone porous support layer may be uneven.

[0017] In one embodiment, the air permeability of the nonwoven fabric substrate is preferably 1.0 to 5.0 cc / cm 2 / sec, more preferably 1.5 to 3.0 cc / cm 2 / sec, more preferably 1.5 to 2.5 cc / cm 2 / sec. When the air permeability is less than 1.0cc / cm 2 When the air permeability is greater than 5.0, the penetration depth of the casting solution for forming the porous support layer in the nonwoven substrate is very shallow, causing the bonding strength between the porous support layer and the nonwoven substrate to weaken, and easily causing the porous support layer to be peeled off from the nonwoven substrate. When the air permeability is greater than 5.0, the penetration of the casting solution for forming the porous support layer in the nonwoven substrate is too large, and even the back side (non-coated side) of the nonwoven substrate can be penetrated, causing coating defects such as pinholes, which is also non-preferred. If the air permeability is within the preferred range, on the one hand, the bonding strength of the porous support layer and the nonwoven substrate is high, and on the other hand, when the casting solution coated with the porous support layer is immersed in the coagulation bath for phase conversion, the diffusion speed of the non-solvent from the back side (non-coated side) to the casting solution coating in the coagulation bath is suitable, and it is easier to form an asymmetric porous support layer structure, which can also cause beneficial effects on the retention amount and diffusion speed of polyamine during the interfacial polycondensation reaction afterwards.

[0018] In one embodiment, the material of the porous support layer can be selected from the following materials alone or in combination: polysulfone, polyethersulfone, sulfonated polyethersulfone, linear aromatic polyamide, polyethylene terephthalate, polyetheretherketone, polyphenylsulfone, polyphenylene oxide, polyethylene, polypropylene, polyacrylonitrile, polyvinyl chloride, etc. Among them, polysulfone, polyethersulfone, polyacrylonitrile, polyethylene, etc. are more preferred. From the aspects of surface tension, chemical stability, rigidity, thermal stability, solubility, etc., polysulfone is further preferred. Specifically, the porous support layer is prepared using a polysulfone material having the following structural formula, which has the advantages of being easily soluble in polar solvents, forming a support layer with good pressure resistance, and being easy to control the surface pore size, so it is particularly preferred.

[0019] In one embodiment, the solvent used to dissolve the polysulfone material can be selected from the following: N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, etc., either alone or in combination. The specific solvent used can be used as long as it can dissolve the polysulfone well and is miscible with the coagulation bath (such as water). In terms of cost, the type of pores in the porous support layer, ease of operation, and safety, N,N-dimethylformamide or N,N-dimethylacetamide is preferred.

[0020] In one embodiment, the thickness of the porous supporting layer is preferably in the range of 10 to 60 μm, more preferably in the range of 30 to 50 μm.

[0021] It should be noted that the thickness of the non-woven fabric substrate and the porous support layer can be obtained by continuously testing 15 samples with a digital thickness meter and taking the average value. The thickness of the porous support layer is obtained by subtracting the thickness of the non-woven fabric substrate from the thickness of the base film.

[0022] In one embodiment, the surface pore size of the porous support layer is preferably in the range of 1 to 100 nm, more preferably 5 to 50 nm, and further preferably 7 to 20 nm. The surface pore size is measured using a field emission scanning electron microscope (FE-SEM). The base film is attached to the sample stage with a conductive adhesive, and the sample is subjected to gold spraying, and then an electron microscope photo is taken at 100,000 times. The base film surface pore size is calculated and measured according to the FE-SEM supporting software scale.

[0023] In one embodiment, the aromatic polyamide desalination layer is a functional layer that plays an actual separation role in the reverse osmosis membrane. Specifically, the polyamide desalination layer is a three-dimensional network cross-linked polyamide formed by an interfacial polycondensation reaction between an aqueous solution of polyvalent aromatic amines and an oily solution of aromatic polyacyl chlorides on the surface of the base membrane. The polyamide desalination layer of the present invention is formed by an interfacial polycondensation reaction between an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride, wherein the aqueous solution contains phosphate esters, and the oily solution contains indole carboxylic acid compounds and methylbenzenes.

[0024] In one embodiment, the so-called polyvalent aromatic amine refers to a compound containing a benzene ring structure and two or more amino groups in the molecule, which is not specifically limited and can be selected from one or more of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 3,5-diaminobenzoic acid, 2,4-diaminobenzenesulfonic acid, 1,3,5-triaminobenzene, N,N-dimethylm-phenylenediamine, N,N-diethylm-phenylenediamine, 3-aminobenzylamine, and 4-aminobenzylamine. From the perspective of easy availability and the salt rejection rate and permeation flux of the resulting membrane, m-phenylenediamine is preferred.

[0025] In one embodiment, the so-called polybasic aromatic acyl chloride refers to a compound containing a benzene ring structure and two or more acyl chloride groups in the molecule, which is not specifically limited and can be selected from one or more of trimesoyl chloride, isophthaloyl chloride, terephthaloyl chloride, biphenyl dichloride, and azophthaloyl dichloride alone or in combination. Considering the ease of availability and the salt rejection rate and permeation flux of the resulting membrane, trimesoyl chloride is preferred.

[0026] In one embodiment, the oil phase solvent for dissolving the polyvalent aromatic acyl chloride is not particularly limited, as long as it is immiscible with water, can form an oil-water interface, and does not dissolve the porous support layer material and the non-woven fabric substrate, such as benzene, halogenated hydrocarbons and alkane solvents. As the benzene solvent, for example, benzene, toluene, etc. can be cited. As the halogenated hydrocarbon solvent, for example, trichlorotrifluoroethane can be cited. As the alkane solvent, for example, straight-chain alkanes such as n-hexane, n-heptane, n-decane, n-undecane, n-dodecane, n-tridecane, n-tetradecane, n-heptadecane, etc. can be cited, and cycloalkanes such as cyclooctane and ethylcyclohexane can also be cited, and isomeric alkanes such as isopar E, isopar G, isoapar L, isopar M, etc. produced by ExxonMobil can also be cited.

[0027] In one embodiment, in addition to the polyvalent aromatic amines and polyvalent aromatic chlorides, as long as they do not hinder the interfacial polycondensation reaction, additives such as co-solvents, complexing agents, acid binding agents, acylation catalysts, phase transfer agents, and organic tin additives may be added to the aqueous or oil phase solution to play a role in regulating molecular diffusion, acylation catalysis, etc. As a co-solvent, it can be selected from: N-methylpyrrolidone, acetone, ethanol, isopropanol, benzene, toluene, m-xylene, 1,3,5-trimethylbenzene, etc.; as a complexing agent, it can be selected from: phosphate ester, tributyl phosphate, 1-methylimidazole, 4-methylpyridine, etc.; as an acid binding agent, it can be selected from: triethylamine, NN-diisopropylethylamine, sodium hydroxide, sodium carbonate, sodium phosphate, etc.; as an antioxidant, it can be selected from: sodium sulfite, sodium pyrosulfite, ascorbic acid, etc.; as an acylation catalyst, it can be listed as caprolactam, N,N-dimethylformamide, 4-dimethylaminopyridine, etc.; as a phase transfer catalyst, it can be selected from: hexamethylphosphoric triamide, tetrabutylammonium bromide, tetramethylammonium bromide, dodecylammonium bromide, etc.

[0028] In one embodiment, in order to facilitate the subsequent production of membrane elements, a dry reverse osmosis membrane can be optionally manufactured. In order to prevent the porous support layer of the membrane from collapsing during the drying process and thus reducing the membrane permeation flux, a moisturizer is required to moisturize the membrane. The moisturizer used for the reverse osmosis membrane of the present invention is not limited in any way, as long as it is a hygroscopic substance that does not damage the reverse osmosis membrane material, and examples thereof include glycerol, citric acid, sodium acetate, glucose, etc.

[0029] Another object of the present invention is to provide a method for preparing a high-flux aromatic polyamide reverse osmosis membrane.

[0030] A method for preparing the high-flux aromatic polyamide reverse osmosis membrane, the method comprising the following steps:

[0031] S1: interfacial polycondensation: m-phenylenediamine and phosphate are dissolved in water to prepare an aqueous solution, and trimesoyl chloride, indole carboxylic acid compounds, organic tin additives, and methylbenzene are dissolved in a solvent to prepare an oil solution; the aqueous solution and the oil solution are reacted on the surface of a polysulfone-based membrane containing a non-woven fabric and a polysulfone porous support layer to form a membrane containing an aromatic polyamide desalting layer through an interfacial polycondensation reaction;

[0032] S2: primary cleaning: the membrane is immersed and cleaned;

[0033] S3: Chemical treatment: immersing the membrane in an aqueous solution of hypochlorite, and then immersing it in an aqueous solution containing a reducing alkali metal salt and an inorganic strong base;

[0034] S4: Secondary cleaning: the membrane is immersed and cleaned;

[0035] S5: Moisturizing and drying: The membrane is immersed in a glycerol aqueous solution, taken out and dried.

[0036] In the present invention, the mass ratio of the S1 intermediate phenylenediamine to trimesoyl chloride is in the range of 15 to 25:1.

[0037] In the present invention, the mass percentage of phosphate in S1 is 0.1% to 1%, the mass percentage of methylbenzene is 5% to 15%, the mass percentage of indole carboxylic acid compound is 0.05% to 0.1%, and the mass percentage of organotin additive is 0.05% to 0.1%, based on the total mass of the oil phase solution.

[0038] In the present invention, the S1 is performed at room temperature.

[0039] In the present invention, the membrane is first immersed in an aqueous solution containing citric acid and glycerol at 50-95° C. for cleaning in S2, and then immersed in water at 50-95° C. for cleaning.

[0040] In the present invention, the temperature range of the aqueous solution containing citric acid and glycerol in S2 is 50-95°C.

[0041] In the present invention, the mass percentage of hypochlorite in the S3 hypochlorite aqueous solution is 0.01% to 0.05%.

[0042] In the present invention, the pH value of the S3 hypochlorite aqueous solution is 7-12, and the pH value of the hypochlorite aqueous solution is adjusted by acid.

[0043] In the present invention, the S4 is to immerse the membrane in pure water for cleaning.

[0044] Another object of the present invention is to provide a use of a high-flux aromatic polyamide reverse osmosis membrane.

[0045] A use of a high-flux aromatic polyamide reverse osmosis membrane, wherein the reverse osmosis membrane is the high-flux aromatic polyamide reverse osmosis membrane or is a reverse osmosis membrane prepared by the above preparation method, and the reverse osmosis membrane is used in the fields of household water purifiers, pure water manufacturing and industrial wastewater treatment.

[0046] In the present invention, when the reverse osmosis membrane is used in the above-mentioned fields, the desalination rate of the reverse osmosis membrane is greater than 98.0% and the permeation flux is 60.0L / (m 2 ·h) and above, after 90 hours of continuous operation, the permeate flux attenuation was less than 15%.

[0047] Compared with the prior art, the beneficial effects of the present invention are:

[0048] (1) The high flux polyamide reverse osmosis membrane provided by the present invention maintains a high desalination rate, and the flux decay is reduced after long-term operation. When the raw water is 25°C and the concentration is 250 mg / L sodium chloride, and the operating pressure is 0.41 MPaG, the desalination rate of the reverse osmosis membrane is above 98.0%, and the permeate flux is 60.0 L / (m 2 ·h) and above, after 90 hours of continuous operation, the permeate flux attenuation was less than 15%.

[0049] (2) The present invention has no major changes in the implementation process compared with the traditional production line, and is easy to industrialize. DETAILED DESCRIPTION

[0050] In order to better understand the specific content of the present invention, the content of the present invention is further described below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0051] Unless otherwise specified, the raw materials used in the following examples or comparative examples are all commercially available conventional raw materials. The main raw material information is shown in the following table:

[0052]

[0053]

[0054] In addition, the indole carboxylic acid compounds such as indole-2-carboxylic acid, indole-3-carboxylic acid, indole-4-carboxylic acid, indole-5-carboxylic acid, indole-6-carboxylic acid, indole-7-carboxylic acid, and 3-indolebutyric acid, and the organotin additives such as dimethyltin dichloride, hexa-n-butyltin dichloride, and tetraphenyltin used in this embodiment are of analytical grade, and their manufacturers are all Shanghai Aladdin Biochemical Technology Co., Ltd.

[0055] The following methods that may be used in the embodiments or comparative examples of the present invention are described:

[0056] Evaluation of salt rejection, permeation flux and long-term operation flux attenuation performance:

[0057] Salt rejection rate and permeation flux are two important parameters for evaluating the separation performance of reverse osmosis membranes. The present invention evaluates the separation performance of reverse osmosis membranes according to the contents of GB / T32373-2005 "Test Method for Reverse Osmosis Membrane".

[0058] The salt rejection rate (R) is defined as: under certain operating conditions, the salt concentration of the reverse osmosis membrane feed solution (C f ) and the permeate salt concentration (C p ) and then divided by the feed solution salt concentration (C f ), as described in the following formula.

[0059]

[0060] The definition of permeation flux is: the volume of water that passes through a unit membrane area per unit time under certain operating conditions, and its unit is L / (m 2 h).

[0061] The reverse osmosis membrane performance test conditions in the present invention are: the feed liquid is a 250 mg / L aqueous solution, the temperature is 25±0.5°C, the solution pH is 7.5±0.5, and the operating pressure is 0.41 MPaG. The membrane flux desalination rate at 30 minutes of continuous operation is taken as the initial performance, and the membrane flux and desalination rate at 90 hours of continuous operation are taken as the performance after long-term operation attenuation. The percentage of flux decrease in 90 hours compared to 30 minutes is calculated as the long-term operation flux attenuation rate.

[0062] Example 1

[0063] The pilot production line is used to prepare the reverse osmosis membrane, and the steps are as follows:

[0064] The polysulfone-based membrane was prepared in a roll-to-roll manner: a DMF solution with a polysulfone mass percentage of 16.5% was evenly coated on a polyester non-woven fabric substrate at 25°C, with a wet coating thickness of 150 μm. After staying in the air for 1.5 seconds, it was immersed in deionized water for 1 minute, and then immersed in deionized water at 70°C for 2 minutes to obtain a rolled base membrane with a width of 400 mm, containing a non-woven fabric substrate and a polysulfone porous support layer.

[0065] The reverse osmosis membrane was prepared in a roll-to-roll manner: the rolled base film with a width of 400 mm obtained above was unrolled again, and then immersed in an aqueous solution with a mass percentage of 2.4% of m-phenylenediamine and a mass percentage of 0.6% of triethyl phosphate for 30 seconds, and then the base film was lifted and pulled out of the aqueous solution tank in the vertical direction, and then the excess aqueous solution on the surface was removed by a rubber squeeze roller, and then the base film surface was evenly coated with an oil phase solution of 0.12% of trimesoyl chloride, 10% of mesitylene, 0.08% of indole-2-carboxylic acid, and 0.08% of dimethyltin dichloride in n-decane. After standing for 30 seconds, the excess oil phase solution on the surface was removed by an oil-displacing rubber roller and an air knife. At this time, the mass ratio of phenylenediamine to trimesoyl chloride was 20:1.

[0066] Then, the membrane was immersed in an aqueous solution containing 6% by mass of citric acid and 3% by mass of glycerol at 80°C for 1 minute (the first water tank), and then immersed in deionized water at 90°C for 2 minutes (the second water tank). Next, the membrane was immersed in a normal temperature sodium hypochlorite aqueous solution with a pH of 7 and a mass percentage of 0.03% for 1 minute (the third water tank), in a normal temperature sodium sulfite aqueous solution with a mass percentage of 1% and a mass percentage of sodium hydroxide for 1 minute (the fourth water tank), in 90°C hot water for 2 minutes (the fifth water tank), in a normal temperature glycerol aqueous solution with a mass percentage of 5% for 1 minute, and then taken out and dried to obtain a polyamide composite reverse osmosis membrane. The desalination rate and permeation flux of the obtained reverse osmosis membrane, and the performance of the membrane after continuous operation for 90 hours were tested, and the results are shown in Table 1.

[0067] Example 2

[0068] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid in Example 1 was replaced by indole-3-carboxylic acid, the temperature of the first water tank was 50° C., and a sodium hypochlorite aqueous solution with a mass percentage of 0.01% was used. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0069] Example 3

[0070] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid in Example 1 was replaced by indole-4-carboxylic acid, the temperature of the first water tank was 95° C., and a sodium hypochlorite aqueous solution with a mass percentage of 0.04% was used. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0071] Example 4

[0072] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid was replaced by indole-5-carboxylic acid and dimethyltin dichloride was replaced by tetraphenyltin. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0073] Example 5

[0074] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid was replaced by indole-6-carboxylic acid and dimethyltin dichloride was replaced by tetraphenyltin. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0075] Example 6

[0076] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid was replaced by indole-7-carboxylic acid and dimethyltin dichloride was replaced by tetraphenyltin. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0077] Example 7

[0078] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid was replaced by 3-indolebutyric acid, dimethyltin dichloride was replaced by tetraphenyltin, mesitylene was replaced by xylene, and triethyl phosphate was replaced by diethyl phosphate. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0079] Example 8

[0080] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that indole-2-carboxylic acid was replaced by indole-4-carboxylic acid, dimethyltin dichloride was replaced by hexa-n-butyl ditin, and the mass percentage of indole-4-carboxylic acid and the organic tin auxiliary hexa-n-butyl ditin was replaced by 0.05%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0081] Example 9

[0082] The reverse osmosis membrane was manufactured in the same manner as in Example 8, except that the mass percentage of indole-4-carboxylic acid and the organic tin auxiliary agent hexa-n-butyl ditin was replaced by 0.1% from 0.05% in Example 8. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0083] Example 10

[0084] The reverse osmosis membrane was manufactured in the same manner as in Example 8 except that the mass percentage of mesitylene in Example 8 was replaced by 5% from 10%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0085] Embodiment 11

[0086] The reverse osmosis membrane was manufactured in the same manner as in Example 8 except that the mass percentage of mesitylene in Example 8 was replaced by 15% from 10%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0087] Example 12

[0088] The reverse osmosis membrane was manufactured in the same manner as in Example 8 except that the mass percentage of triethyl phosphate in Example 8 was replaced by 0.1% from 0.6%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0089] Embodiment 13

[0090] The reverse osmosis membrane was manufactured in the same manner as in Example 8 except that the mass percentage of triethyl phosphate in Example 8 was replaced by 1.0% from 0.6%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0091] Embodiment 14

[0092] The reverse osmosis membrane was manufactured in the same manner as in Example 8, except that the pH value of the sodium hypochlorite in the third water tank in Example 8 was adjusted from 7 to 9. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0093] Embodiment 15

[0094] The reverse osmosis membrane was manufactured in the same manner as in Example 8, except that the pH value of the sodium hypochlorite in the third water tank was adjusted from 7 to 12, and the sodium hypochlorite aqueous solution was replaced with a sodium hypochlorite aqueous solution with a mass percentage of 0.05%. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0095] Example 16

[0096] The reverse osmosis membrane was manufactured in the same manner as in Example 1 except that the triethyl phosphate in Example 1 was replaced by diethyl phosphate. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0097] Embodiment 17

[0098] The reverse osmosis membrane was manufactured in the same manner as in Example 1 except that 1,3,5-trimethylbenzene was replaced by m-xylene. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0099] Embodiment 18

[0100] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that 1,3,5-trimethylbenzene in Example 1 was replaced by m-xylene, and the mass ratio of m-phenylenediamine to trimesoyl chloride was changed from 20:1 to 15:1 while the mass percentage of trimesoyl chloride was maintained unchanged. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0101] Embodiment 19

[0102] The reverse osmosis membrane was manufactured in the same manner as in Example 1, except that 1,3,5-trimethylbenzene in Example 1 was replaced by m-xylene, and the mass ratio of m-phenylenediamine to trimesoyl chloride was changed from 20:1 to 25:1 while the mass percentage of trimesoyl chloride was maintained unchanged. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0103] Comparative Example 1

[0104] Compared with Example 1, the reverse osmosis membrane was manufactured in the same manner as Example 1, except that triethyl phosphate was not added to the m-phenylenediamine aqueous phase solution, and indole-2-carboxylic acid, mesitylene and dimethyltin dichloride were not added to the trimesoyl chloride oil phase solution. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0105] Comparative Example 2

[0106] Compared with Example 1, the reverse osmosis membrane was manufactured in the same manner as Example 1, except that indole-2-carboxylic acid, mesitylene and dimethyltin dichloride were not added to the trimesoyl chloride oil phase solution. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0107] Comparative Example 3

[0108] Compared with Example 1, a reverse osmosis membrane was manufactured in the same manner as Example 1, except that indole-2-carboxylic acid and dimethyltin dichloride were not added to the trimesoyl chloride oil phase solution. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0109] Comparative Example 4

[0110] Compared with Example 1, a reverse osmosis membrane was manufactured in the same manner as Example 1, except that dimethyltin dichloride was not added to the trimesoyl chloride oil phase solution. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0111] Comparative Example 5

[0112] Compared with Example 1, the reverse osmosis membrane was manufactured in the same manner as Example 1, except that indole-2-carboxylic acid was not added to the trimesoyl chloride oil phase solution. The salt rejection rate and permeation flux of the obtained reverse osmosis membrane were tested, and the membrane performance after continuous operation for 90 hours was tested. The results are shown in Tables 1 and 2.

[0113] Table 1 Reaction material list

[0114]

[0115]

[0116]

[0117] Table 2 Reverse osmosis membrane performance

[0118]

[0119]

[0120] It can be seen from Comparative Examples 1 to 3 that although the addition of phosphate esters to the aqueous solution and methylbenzene to the oil solution can increase the flux of the membrane, the flux of the membrane decays significantly during long-term use.

[0121] It can be seen from Comparative Examples 4 to 5 that, although the membrane flux is further improved by adding an organic tin additive alone or adding an indole carboxylic acid compound to the oil phase solution, the flux attenuation rate of the membrane is further increased during long-term use.

[0122] It can be seen from Examples 1 to 19 and Comparative Examples 4 to 5 that the addition of an organic tin additive and an indole carboxylic acid compound to the oil phase solution, combined with the addition of a phosphate ester to the aqueous phase, not only achieves a high flux of the reverse osmosis membrane, but also significantly reduces the flux attenuation rate of the reverse osmosis membrane over a long period of use.

[0123] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

[0124] The embodiments of the present invention only require that the process of the existing production line remain unchanged and, by adding additives, the flux attenuation amplitude of the reverse osmosis membrane after long-term operation can be reduced while maintaining high permeation flux and high desalination rate, and thus has good applicability in the industry.

Claims

1. A high-flux aromatic polyamide reverse osmosis membrane, comprising a non-woven fabric, a polysulfone porous support layer and a polyamide desalination layer, characterized in that: The polyamide desalting layer is formed by an interfacial polycondensation reaction between an aqueous solution of m-phenylenediamine and an oily solution of trimesoyl chloride; Wherein, the oil phase solution contains an indole carboxylic acid compound and an organic tin additive; In the molecular structure of the indole carboxylic acid compound, the hydrogen on the nitrogen atom of the indole ring is not substituted, the indole ring has only one substituent, and the substituent is an alkyl acid substituent containing 1 to 5 carbon atoms.

2. The reverse osmosis membrane according to claim 1, characterized in that The indole carboxylic acid compound is selected from one or more of indole-2-carboxylic acid, indole-3-carboxylic acid, indole-4-carboxylic acid, indole-5-carboxylic acid, indole-6-carboxylic acid, indole-7-carboxylic acid and 3-indolebutyric acid.

3. The reverse osmosis membrane according to claim 1 or 2, characterized in that: In the molecular structure of the organic tin auxiliary agent, at least two alkyl groups or phenyl groups are directly connected to the tin atom.

4. The reverse osmosis membrane according to claim 3, characterized in that The organic tin auxiliary agent is selected from one or more of dimethyltin dichloride, hexa-n-butyltin, and tetraphenyltin.

5. The reverse osmosis membrane according to claim 1, characterized in that The aqueous phase solution contains phosphate; And / or, the oil phase solution contains methylbenzene.

6. The reverse osmosis membrane according to claim 5, characterized in that The aqueous phase solution contains triethyl phosphate; And / or, the oil phase solution contains 1,3,5-trimethylbenzene.

7. A method for preparing a high-flux aromatic polyamide reverse osmosis membrane according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1: interfacial polycondensation: m-phenylenediamine and phosphate are dissolved in water to prepare an aqueous solution, and trimesoyl chloride, indole carboxylic acid compounds, organic tin additives, and methylbenzene are dissolved in a solvent to prepare an oil solution; the aqueous solution and the oil solution are reacted on the surface of a polysulfone-based membrane containing a non-woven fabric and a polysulfone porous support layer to form a membrane containing an aromatic polyamide desalting layer through an interfacial polycondensation reaction; S2: primary cleaning: the membrane is immersed and cleaned; S3: Chemical treatment: immersing the membrane in an aqueous solution of hypochlorite, and then immersing it in an aqueous solution containing a reducing alkali metal salt and an inorganic strong base; S4: Secondary cleaning: the membrane is immersed and cleaned; S5: Moisturizing and drying: The membrane is immersed in a glycerol aqueous solution, taken out and dried.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the S1 interphenylenediamine to trimesoyl chloride is in the range of 15 to 25:1; And / or, the mass percentage of phosphate in S1 is 0.1% to 1%, the mass percentage of methylbenzene is 5% to 15%, the mass percentage of indole carboxylic acid compound is 0.05% to 0.1%, and the mass percentage of organotin additive is 0.05% to 0.1%, based on the total mass of the oil phase solution.

9. The preparation method according to claim 8, characterized in that: The S1 is carried out at room temperature; And / or, in S2, the membrane is first immersed in an aqueous solution containing citric acid and glycerol at 50-95°C for cleaning, and then immersed in water at 50-95°C for cleaning; and / or, the mass percentage of hypochlorite in the S3 hypochlorite aqueous solution is 0.01% to 0.05%; And / or, the pH value of the S3 hypochlorite aqueous solution is 7 to 12, and the pH value of the hypochlorite aqueous solution is adjusted by acid; And / or, the S4 is to immerse the membrane in pure water for cleaning.

10. Use of a high-flux aromatic polyamide reverse osmosis membrane, wherein the reverse osmosis membrane is the high-flux aromatic polyamide reverse osmosis membrane according to any one of claims 1 to 6, or is a reverse osmosis membrane prepared by the preparation method according to any one of claims 7 to 9, characterized in that: The reverse osmosis membrane is used in the fields of household water purifiers, pure water production and industrial wastewater treatment.

11. The use according to claim 10, characterized in that When the reverse osmosis membrane is used in the above-mentioned fields, the desalination rate of the reverse osmosis membrane is greater than 98.0% and the permeation flux is 60.0L / (m 2 ·h) and above, after 90 hours of continuous operation, the permeate flux attenuation was less than 15%.

Citation Information

Patent Citations

  • Composite semipermeable membrane and method for producing same

    CN102665881A

  • Separation membrane element and method for producing composite semipermeable membrane

    CN103025412A

  • Composite polyamide membrane

    CN104470627A

  • Composite semipermeable membrane and production thereof

    CN105026022A

  • Composite polyamide membrane including tri-hydrocarbyl phosphate

    CN105377406A